Review artikel: Macam - macam Pengikat dan Pengisi Pada Sediaan Tablet - dewi rahmawati (CV. Melek Literasi Press, 2024)
A tablet is a solid dosage form which contains medicinal ingredients, either with or without fillers. In tablet preparations, apart from the active substance, there are excipients or additional ingredients, such as fillers and binders. The addition of fillers and binders to tablet preparations aims to facilitate the preparation of dosage forms, improve the physical properties of tablets, and increase the cohesiveness of the powder to be made into tablets. In this analysis, the method used is based on literature reviews from search sources on Google Scholar. The higher the concentration and amount of binder can increase the granule size and friability of the tablet, however, in the requirements for making tablets with good hardness and friability, a minimum amount of binder is used. Based on the data from observations that have been made, it can be concluded that PVP, Gelatin, Gom Arab, Putih Telur, Amilum, Manitol Sukrosa, Copovidin, Hidroksida Propil Selulosa, Metil Selulosa, Laktosa can be used as an excipient/binding agent because it can produce physical properties that can meet the requirements for tablets, while excipient/filling agents such as Lactose, Filler - Binder can be used because it produces physical properties that can meet the requirements. tablet requirements.